2022
DOI: 10.1186/s12887-022-03481-1
|View full text |Cite
|
Sign up to set email alerts
|

The value of urinary gonadotropins in the diagnosis of central precocious puberty: a meta-analysis

Abstract: Background The gonadotropin-releasing hormone (GnRH) stimulation test is time-consuming, invasive, and costly. However, it is the diagnostic gold standard for central precocious puberty (CPP), which in girls is defined as the onset of secondary sexual characteristics before the age of 8 years accompanied by breast buds, accelerated growth, and advanced bone age. This meta-analysis was performed to compare the diagnostic value of urinary gonadotropins and the GnRH stimulation test for CPP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although home urinary samples could underlie some limitations concerning the correct collection procedure, as reported by Xu et al [ 19 ], it represents an undoubtedly valid tool as a non-invasive method to diagnose CPP. Concerning the storage of urinary samples, the choice not to freeze but to store urines at a controlled temperature of 4 °C derives from the need to ensure greater stability of the LH molecule, in accordance with what was established by Demir et al[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although home urinary samples could underlie some limitations concerning the correct collection procedure, as reported by Xu et al [ 19 ], it represents an undoubtedly valid tool as a non-invasive method to diagnose CPP. Concerning the storage of urinary samples, the choice not to freeze but to store urines at a controlled temperature of 4 °C derives from the need to ensure greater stability of the LH molecule, in accordance with what was established by Demir et al[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from last decade reporting data on FMV urines or random urines have shown good usefulness, with sensitivity from 65% to 92% and specificity from 63% to 100% ( Demir et al , 2021 ; Zhan et al , 2021 ). A meta-analysis from Xu et al (2022) that retained six studies, in spite of heterogeneous collecting protocols (collection protocols, sample treatment prior to analysis) and analytical techniques, revealed an overall sensitivity of 79% and specificity of 84%. Comparisons of diagnostic thresholds from different studies must consider these pre-analytical and assay method differences.…”
Section: Discussionmentioning
confidence: 99%
“…Among the newest laboratory data considered are levels of inhibin B, SHBG, and urinary gonadotropins. However, these tests are not easily accessible in all centers, can be expensive, and do not yet have a well-defined cut-off level [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%